Hedges in English Research Articles by Kurdish and English Native Authors - Anjuman Muhammad Sabir (Zanco Journal of Humanity Sciences)
This paper examines the types and frequency of hedges written by Kurdish authors (KA) and English authors (EA) in different sections of English research articles in the field of linguistics during the period 2016-2018, based on the taxonomy of hedges proposed by Hyland (1998).  Hence, a corpus of twenty research articles published in national and international journals were randomly selected and analyzed in terms of frequency and type. The choice of hedging devices is basically tactical since authors from both groups incline to use appropriate hedging strategies to express claims with accuracy, attention and humility. The results show that generally English authors use more hedges compared to Kurdish authors, this could be due to different cultural background, nationality, language proficiency and rhetorical differences between the two languages. English authors use lexical verbs, adverbs, adjectives and nouns in research articles more frequently than their Kurdish counterparts. The findings also provide some pedagogical implications for teachers in that they can employ various techniques to help students improve their ability in using hedging devices; they should also make students be aware of different types of hedging devices.